Nation brand image and trust level of foreign citizens - Damayanti, Trie; Dida, Susanne; Hidayat, Dadang Rahmat; Cho, Sung Kyum (Universitas Padjadjaran, 2022)
The state is an organization with a power structure and the population as members of the state. The state itself is an entity that interacts with other entities that can consist of other countries and their inhabitants, rules, and products. Because of this, a country needs an identity that can distinguish the country from other countries. The identity of a country is not the same as the identity of a product because a country is bound by history and images attached to foreign citizens’ minds. This inherent image is usually used to form a nation’s brand image. This study aims to discover how Malaysia’s nation brand image contributes to the trust of foreign nationals visiting their country by using a constructivist qualitative approach as a research method. It turns out that the results of the study show that the most powerful thing in determining Malaysia’s brand image is not tourism promotion. As a country with an image of different cultures, Malaysia will use this potential to visualize its tourism promotion to keep those images stronger. However, the experience of Indonesian citizens in interacting with the Malaysian state, with infrastructure, state norms, and citizens, is a determinant of how Indonesian citizens perceive Malaysia. What is inherent in the results of the experience of interacting in Malaysia is what Indonesian citizens will convey to others. Therefore, a comprehensive strategy is needed to build a national brand image of Malaysia because what sticks in mind as an image of Malaysia in foreign nationals will show their trust in the country.